“New Mediterranean Biodiversity Records” (March 2017) - L. LIPEJ; I. ACEVEDO; E.H.K. AKEL; A. ANASTASOPOULOU; A. ANGELIDIS; E. AZZURRO; L. CASTRIOTA; M. ÇELIK; L. CILENTI; F. CROCETTA; A. DEIDUN; A. DOGRAMMATZI; et al. (Mediterranean Marine Science, 2017)
This Collective Article presents information on 22 species belonging to 5 Phyla, arranged geographically from from west to east. The new records were found in 8 countries as follows: Spain: first record of the two scarcely known nemerteans Baseodiscus delineatus and Notospermus geniculatus in Formentera; Malta: second record of the alien fish Lagocephalus sceleratus; Italy: the alien polychaete Syllis pectinans and the isopod Paranthura japonica, as well as the cryptogenic opisthobranch Anteaeolidiella lurana, were found in the fouling assemblages along the docks of the port of Livorno. New decapod records are reported from Sicily (the alien Callinectes sapidus and the native Pachygrapsus maurus) and Apulia (Percnon gibbosus and Procambarus clarkii); the lesser amberjack Seriola fasciata extended its geographical range to the Egadi Isands and Siganus luridus was documented for the first time along the Ionian coasts of Apulia and Calabria. Slovenia: the first record of the alien bivalve Brachidontes pharaonis is reported, together with a survey of up to date Adriatic records. Greece: the first record of the gastropod Rhinoclavis kochi is reported from Gavdos island. In addition, two records of endangered and rare cartilaginous fish were reported, namely, the shark Hexanchus griseus and the ray Leucoraja fullonica, as well as additional records of Siganus luridus for Lesvos and Malleus regula and Fulvia fragilis from Astypalaia. Turkey: the black wing flyingfish Hirundichthys rondeletii is reported for the very first time from the Black Sea. Egypt: the Indo-Pacific crab Halimede ochtodes is reported as established in Port Said. In addition, biometric parameters and meristic counts are reported for Anthias anthias in Damietta. Cyprus: the alien opisthobranch gastropod Bursatella leachii is reported for first time.